2002
DOI: 10.1002/cncr.10834
|View full text |Cite
|
Sign up to set email alerts
|

Cancer among Hispanic women in South Florida: An 18‐year assessment

Abstract: We experimentally examine a dilute suspension of non‐neutrally buoyant spherical particles migrating in a simple mixing tank at small but finite Reynolds numbers. We observe that the particles spontaneously migrate to repeatable non‐trivial asymptotic locations within toroidal structures, located above and below at‐disk impellers. The asymptotic migration positions include both the exact center of the torus and intermediate higher‐order cluster locations within the flow whose stability is dependent on flow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…Although incidence rates for Latinos of specific origins could not be calculated, the data on screening and known cancer risk factors among specific Latino groups suggest several general points: first, not all Hispanic populations in the U.S. are alike; 67 second, data reported from various studies on Hispanic populations may not be comparable if the underlying Hispanic populations do not share the same origins, cultural traditions, and immigration status; [68][69][70][71][72] and third, collection of specific Hispanic origin needs to be increased in general population and demographic statistics as well as in the records of persons diagnosed and dying from cancer. 68,73 The cancer incidence data reported here on 90% of U.S. Latinos mirror findings of many other studies on various Latino groups or areas, 45,68,71,[74][75][76][77][78][79][80][81] with a few exceptions. Rate estimates (Trapido et al reported higher rates of cancers of the oral cavity and thyroid in white Latinas 81 and lower rates of stomach cancer in white Latinos, 80 compared with white non-Hispanic women and men, respectively), rank order of top cancer sites (Trapido et al 79 reported for the U.S. that the top 5 cancer sites for Latinos were prostate, lung, colon, stomach, and rectum and for Latinas, cancers of the breast, colon, lung, cervix, and uterine corpus.…”
Section: Cancer In Latinosmentioning
confidence: 99%
See 2 more Smart Citations
“…Although incidence rates for Latinos of specific origins could not be calculated, the data on screening and known cancer risk factors among specific Latino groups suggest several general points: first, not all Hispanic populations in the U.S. are alike; 67 second, data reported from various studies on Hispanic populations may not be comparable if the underlying Hispanic populations do not share the same origins, cultural traditions, and immigration status; [68][69][70][71][72] and third, collection of specific Hispanic origin needs to be increased in general population and demographic statistics as well as in the records of persons diagnosed and dying from cancer. 68,73 The cancer incidence data reported here on 90% of U.S. Latinos mirror findings of many other studies on various Latino groups or areas, 45,68,71,[74][75][76][77][78][79][80][81] with a few exceptions. Rate estimates (Trapido et al reported higher rates of cancers of the oral cavity and thyroid in white Latinas 81 and lower rates of stomach cancer in white Latinos, 80 compared with white non-Hispanic women and men, respectively), rank order of top cancer sites (Trapido et al 79 reported for the U.S. that the top 5 cancer sites for Latinos were prostate, lung, colon, stomach, and rectum and for Latinas, cancers of the breast, colon, lung, cervix, and uterine corpus.…”
Section: Cancer In Latinosmentioning
confidence: 99%
“…Some differences may be attributed to variation in time periods under study, 68,75,79,81,82 the specific geographies and thus varying origins of the local Hispanic population, 67,72 or limited statistical power to detect differences. 71,83 U.S. Latinos have lower rates of several cancers that are higher in affluent, industrialized countries where tobacco use, obesity, and physical inactivity may be more prevalent. Several cancer sites with higher incidence rates in Latinos have infectious etiologies: human papilloma virus (HPV) in cervical cancer, Helicobacter pylori (H. pylori) in stomach cancer, 84 and Hepatitis B virus (HBV) and Hepatitis C virus (HCV) in liver cancer (and hepatocellular carcinoma).…”
Section: Cancer In Latinosmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cancer incidence rates from SEER for Hispanic subgroups are generally not available. To date, several studies have explored cancer incidence and mortality differentials between all Hispanics and White non-Hispanics in Florida [2,3,[17][18][19]. By drawing no distinction among the different Hispanic subgroups researchers extrapolate data from one Hispanic subgroup to another where this extrapolation may not always be valid and, in fact, may be misleading [20].…”
Section: Introductionmentioning
confidence: 99%
“…Pap screening rates were lowest among black Floridians relative to blacks residing in 29 other states with sufficient data to report race-specific rates [58]. Finally, higher cervical cancer rates in Hispanics [59,60], which comprise 19% of the state population, may also partially account for the higher rates of cervical cancer in white Floridians. Additional research and prevention activities directed at increasing pap screening rates in Florida are needed.…”
Section: Findings For Tobacco-associated Cancers With Lower Smoking Amentioning
confidence: 95%